ІНТЕЛЕКТУАЛІЗАЦІЯ ДІЯЛЬНОСТІ НАФТОГАЗОВИХ ПІДПРИЄМСТВ ШЛЯХОМ ІНСТИТУЦІЙНИХ ЗМІН В ОСВІТНІЙ СФЕРІ - Кісь C Я; Кісь, Г Р (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article is devoted to topical issues of activity of economic entities of the domestic oil and gas complex (OGC), concerning the necessity and prerequisites for achieving a high level of intellectualization. Attention is focused on the fact that the main problems of implementation and effectiveness of intellectualization processes are related to the imperfection of the organization by branch enterprises of the development processes of management and executive personnel. The necessity of the transition of OGC enterprises and the establishment of higher oil and gas education to a new format of mutually beneficial relations is substantiated. The basis for this should be institutional changes in the form of the creation and functioning of an innovative educational institution - the sectoral corporate university of human resources development (SCUHRD). The organizational, legal and economic foundations of the operation of the SCUHRD are proposed. The main advantages of the SCUHRD activity are determined taking into account the organizational prerequisites, experience and scientific achievements of the Ivanovo-Frankivsk National Technical University of Oil and Gas (IFNTUOG) as an oil and gas university. The expected effect (social and economic) of the activity of the SCUHRD on the basis of public-private partnership (PPP) is proposed to be considered in the short and long term. A forecast is made of the results of the activity of the SCUHRD in the context of the impact on the effectiveness of the implementation of personnel development processes and the activities of enterprises of the Ukrainian NGC as a whole.